The Effects of Food Intake and Eating Behavior on Sleep Quality in Adolescents - Nisa Nur KAYA; Muhammet Ali CEBIRBAY (Amerta Nutrition, 2022)
Background: Food and eating behaviors can be related to nutrition as well as sleep for healthy society. Objectives: The aim of the study is to examine the eating behaviors of adolescents and the effect of some foods on sleep quality in adolescence. MethodS: The study was carried out as a survey model of 580 adolescents in Konya, Turkey. The questionnaire consists of demographic features and anthropometric measurements, Pittsburg Sleep Quality Index (PSQI), Eating Behavior Scale (EBS), and 24-hour recalled food consumption record used for evaluation of daily nutrient intakes. The SPSS (ver. 22) software was used to analyze the data. Results: PSQI score was 5.79±0.17 in girls and 5.27±0.15 in boys, with a significant difference (p=0.022) and sleep quality was found to be good in 42.4% and poor in 57.6%. Sleep duration (p=0.011), sleep disturbances (p=0.002), daytime dysfunction (p=0.000) were differed by gender. The mean of EBS score was found to be 211.04±61.32, differed between girls and boys (p<0.05). Also, the EBS score differed by night eating (p=0.000). Total energy (p=0.001), protein (p=0.001), carbohydrate (p=0.003), B1 (p=0.028), B6 (p=0.006), niacin (p=0.000), folic acid (p=0.001), B12 (, Zn, and Fe daily intake changed between girls and boys (p<0.05). Conclusion: Adolescents with poor sleep quality, poor eating behavior should consider night eating is to determine if it may be associated with their sleep.